ALL THE NEW IS THE WELL FORGOTTEN OLD: AUTOPERICARDIAL MITRAL ANNULOPLASTY FOR DEGENERATIVE DEFECTS - S.A. ZHURKO; A.B. GAMZAEV; K.M. AMINOV; P.V. PIMENOVA (Паёми Сино, 2021)
Objective: To present the first-hand results of a modified mitral annuloplasty (MA) with an autopericardial strip (APS) in degenerative mitral valve disease (DMVD).